Crossing Borders, Shifting Identities: The Transnational Journey of Wafa Faith Hallam from Morocco to America - Bekkaoui, Tariq (International Journal of Language and Literary Studies, 2024)
Wafa Faith Hallam's memoir, The Road from Morocco, presents a profound narrative that spans the personal and cultural journeys of two Moroccan women, Wafa and her mother Saadia, against the backdrop of postcolonial shifts and Western influences. Born into a conservative Muslim society and later migrating to America, their stories intricately map the contours of identity, freedom, and resistance within and across the boundaries of tradition and modernity. Wafa's transition from a lifestyle characterized by personal freedom in Morocco to confronting the harsh realities of domestic violence in America, alongside Saadia's quest for autonomy and escape from patriarchal constraints at home, reveals a profound disillusionment. Both women anticipated that America would offer them romance and liberation, only to encounter even more intense patriarchal oppression. The idea conveyed in the narrative is that the West, contrary to its image as a bastion of gender equality and freedom, can exhibit even more severe forms of gender despotism than those found in traditional Oriental societies. The memoir presents a deconstructive counternarrative that critiques both the West and Western feminism. The Road from Morocco is not merely a recounting of personal history but a significant contribution to the discourse on postcolonial identity, gender dynamics, and the immigrant experience, inviting a reevaluation of simplistic paradigms of gender liberation and oppression.